Theories of stagnation in historical perspective - Roger E. Backhouse; Mauro Boianovsky (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
This article traces some of the historical roots of current debates about secular economic stagnation, involving L. Summers, R. Gordon, and others. We focus on early contributions by Alvin Hansen and John A. Hobson. Although Hansen has been the main influence on the secular stagnation literature, Hobson's suggested link between economic inequality and stagnation is of interest in view of T. Piketty's recent claim about the connection between slower growth and inequality. E. Domar and P. Samuelson, Hansen's students at Harvard, elaborated economic growth and multiplier-accelerator models as follow-ups to Hansen's original treatment. Domar called attention to Hobson's insight about underconsumption, increasing capacity, and deficient aggregate demand. We conclude that the range of positions held today concerning stagnation and inequality is large, as it was earlier in the history of thought.
Keywords: B22; E12; 330; secular stagnation; inequality; underconsumption; Hansen; Summers